Accuracy of ultrasound-guided fine needle aspiration cytology (US-FNAC) to detect axillary involvement in breast cancer - Gouveia, Maria Carolina; Santos, Candice Lima; Pereira, Isabel Cristina; Souza, Ariani Impieri (Brazilian Journal of Oncology, 2021)
Introduction: Axillary involvement is one of the main prognostic factors in breast cancer. This study aimed to assess the accuracy of ultrasound-guided fine needle aspiration cytology (US-FNAC) to detect axillary involvement in breast cancer and to compare with other methods of axilla assessment: axillary palpation (AP) and isolated axillary ultrasound (A-US). Methods: A retrospective accuracy study was performed using data from medical records of patients assisted at a breast cancer service in Recife, Brazil, between 2013 and 2017. A histopathological result (sentinel lymph node and/or axillary dissection) was adopted as a gold standard. Sensitivity, specificity, accuracy, positive predictive value (PPV) and negative predictive value (NPV) of the AP, the A-US and US-FNAC were calculated. Results: 206 tumors were analyzed. The AP was truly positive in 34.0% of the results similar values were obtained for A-US (36.4%). The lowest incidence of false negative was in the US-FNAC (16.5%). Axillary involvement was identified in 82 (39.8%) cases. The US-FNAC was performed in 79 cases, 51 (64.5%) were identified as true positive and 13 (16.5%) were false negative. When analyzing the comparative results of AP, A-US and the US-FNAC of the axilla with histopathology, it was observed that AP presented an accuracy of 69.9% (95%CI=63.1-76.1), better than the A-US, which its accuracy was 68% (95%CI=61.1-74.3). The US-FNAC showed high specificity (100%, 95%CI=81.9-100%), of PPV at 100% (95%CI=94.3-100%), but with a low NPV (53.6%, 95%CI=33.9-72.5). The best NPV was the AP (59.7%, 95%CI=50.5-68.4). The US-FNAC accuracy was 83.5% (95%CI=73.591.0). Conclusion: The good accuracy associated to the high specificity and the PPV of the US-FNAC suggests it to be a promising examination in the diagnosis of axillary involvement in breast cancer and an ally to better define therapeutic conducts.
Keywords: Neoplasias mamárias; Biópsia com agulha fina; Terapia neoadjuvante; Linfonodo sentinela.